Full-fat Hermetia illucens larvae meal as a sustainable soybean meal substitute in laying hen diets: effects on performance, egg quality, and shelf-life - Simone Mancini; Andrea Vitali; Marco Meneguz; Carlotta Volterrani; Sabrina Battisti; Sofia Cucci; Andrea Carvelli; Davide Santori; Giampiero Grossi; Eleonora Batistini; Nicola Lacetera; Nicola Ferrarini; et al. (Italian Journal of Animal Science)
This study investigates the feasibility of replacing soybean meal (SBM) with full-fat Hermetia illucens meal (HIM) in the diets of Lohmann Brown-Classic hens and its impact on laying performance, egg quality, and storage life. Over an 8–week trial, 108 hens were divided into three dietary groups: SBM, HIM50 (50% SBM replaced with HIM), and HIM100 (100% SBM replaced with HIM). The diets were isoenergetic and isoproteic, supplemented with essential amino acids. Feed intake, egg production, and quality were monitored daily, with bi-weekly evaluations of egg quality fresh and after 21 days of storage at ambient temperature. Results indicated that partial and total replacement of SBM with HIM had no significant effect on feed intake, laying rate, egg mass, or feed conversion index. However, total replacement (HIM100) significantly increased live weight. Egg quality parameters such as egg weight, shell weight, albumen weight, yolk weight, yolk index, Haugh unit, and yolk colour were unaffected by the diets. Notably, a significant reduction in eggshell thickness was observed in the HIM100 group, and albumen index increased with the HIM50 and HIM100 diets. The study concludes that HIM can be a viable alternative protein source to SBM in laying hen diets without adverse effects on production and egg quality. Further research is recommended to assess the economic and environmental sustainability of HIM on a commercial scale.